2021
DOI: 10.3390/molecules26082205
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Prenyl Chalcone as a Competitive Lipoxygenase Inhibitor: Screening, Biochemical Evaluation and Molecular Modeling Studies

Abstract: Cyclooxygenase (COX) and lipoxygenase (LOX) are key targets for the development of new anti-inflammatory agents. LOX, which is involved in the biosynthesis of mediators in inflammation and allergic reactions, was selected for a biochemical screening campaign to identify LOX inhibitors by employing the main natural product library of Brazilian biodiversity. Two prenyl chalcones were identified as potent inhibitors of LOX-1 in the screening. The most active compound, (E)-2-O-farnesyl chalcone, decreased the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The plant lipoxygenase pathway is in many aspects equivalent to the “arachidonic acid cascades” in animals . For this reason, the in vitro inhibition of lipoxygenase (LOX) constitutes a good model for the screening of plants with anti-inflammatory potential . LOXs are sensitive to antioxidants, and most of their action may consist of inhibition of lipid hydroperoxide formation due to scavenging of lipid peroxyl radicals formed in the course of enzyme peroxidation.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant lipoxygenase pathway is in many aspects equivalent to the “arachidonic acid cascades” in animals . For this reason, the in vitro inhibition of lipoxygenase (LOX) constitutes a good model for the screening of plants with anti-inflammatory potential . LOXs are sensitive to antioxidants, and most of their action may consist of inhibition of lipid hydroperoxide formation due to scavenging of lipid peroxyl radicals formed in the course of enzyme peroxidation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…65 For this reason, the in vitro inhibition of lipoxygenase (LOX) constitutes a good model for the screening of plants with anti-inflammatory potential. 66 LOXs are sensitive to antioxidants, and most of their action may consist of inhibition of lipid hydroperoxide formation due to scavenging of lipid peroxyl radicals formed in the course of enzyme peroxidation. From one study, it has been shown that ethyl acetate extract of the leaves and flowers of Mikania micrantha exhibited 98 and 185 μg/mL IC 50 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Another flavonoid subclass, chalcone, was tentatively identified (compound 3), sharing common fragments with compound 7, including m/z 323.1281, 255.0615 and 254.0567. Various pharmacological effects of the prenylated chalcones (e.g., compound 3) have been reported in the literature, including the anticancer activity [67][68][69][70][71]. Compounds 1 and 2 differ from previously isolated and fully characterised prenyl stilbenes such as compounds 4 and 5 in one extra oxygen atom (15.99-16.00 Da) and share their characteristic fragments at m/z 188.0480, and 144.0580.…”
Section: Biochemometric and Lcms Metabolomic Identification Of Cytotoxic Metabolites Of Ap-1mentioning
confidence: 99%
“…Chalcones, , in particular, flavonoids, are natural products that display a broad spectrum of activities such as anticancer, antibacterial, antifungal, antimalarial, antidiabetic, anti-inflammatory, lipoxygenase inhibition, , and antioxidant . Representatives of this class of compounds are already used in clinical practice or are undergoing clinical trials, including metochalcone, sofalcone, isoliquiritigenin, xanthohumol, hesperidin, and methylchalcone. , …”
Section: Introductionmentioning
confidence: 99%